2017
DOI: 10.1007/s00284-017-1226-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Abundance, Diversity, and Activity of Ammonia-Oxidizing Bacteria in Coastal Sediments of the Liaohe Estuary

Abstract: Ammonia-oxidizing bacteria (AOB) play an important role in nitrification in estuaries. The aim of this study was to examine the spatial abundance, diversity, and activity of AOB in coastal sediments of the Liaohe Estuary using quantitative PCR, high-throughput sequencing of the amoA gene coding the ammonia monooxygenase enzyme active subunit, and sediment slurry incubation experiments. AOB abundance ranged from 8.54 × 10 to 5.85 × 10 copies g of wet sediment weight and exhibited an increasing trend from the Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…A similar phylum composition structure was found in previous wetland soil investigations in the Jiulong River estuary [21] and intertidal sediments in the Yellow Sea [22]. As the dominant phylum in soil samples, Proteobacteria was involved in nitrification, denitrification, and sulphuration [23,24]. Playing the leading role in a large number of processes related to the nitrogen cycle and sulfur…”
Section: Composition and Structure Of The Bacterial Communitysupporting
confidence: 78%
“…A similar phylum composition structure was found in previous wetland soil investigations in the Jiulong River estuary [21] and intertidal sediments in the Yellow Sea [22]. As the dominant phylum in soil samples, Proteobacteria was involved in nitrification, denitrification, and sulphuration [23,24]. Playing the leading role in a large number of processes related to the nitrogen cycle and sulfur…”
Section: Composition and Structure Of The Bacterial Communitysupporting
confidence: 78%
“…Öre River), whereas Nitrosospira ‐like OTUs were confined to the rivers, indicating a preference for freshwater. Both genera have, however, previously been found in Baltic Sea waters and sediments (Kim et al ., ; Vetterli et al ., ), and in sediments (Chang et al ., ) and waters (Bano and Hollibaugh, ; O'Mullan and Ward, ; Kim et al ., ) from multiple localities. It is not understood what governs the distribution of the two genera, possibly as a consequence of difficulties associated with correlating single environmental factors to complex combinations of variables shaping AOB diversity in dynamic environments (Francis et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The primer sequences for the soil nitrification microbial amoA gene were A26F (5′-GACTACATMTTCTAYACWGAYTGGGC-3′) and A416R (5′-GGKGTCATRTATGG WGGYAAYGTTGG-3′) ( Francis et al, 2005 ). The AOA amoA and AOB amoA genes were amplified with primer sequences amoA -1F (5′-GGGGTTTCTACTGGTGGT-3′) and amoA -1R (5′-CCCCTCKGSAAAGCCTTCTTC-3′), respectively ( Chang et al, 2017 ). The reaction system was as follows: 10 μM upstream primer and downstream primer 1 μL, 1 μL SYBR ® PremixExTaq™II (TliRNaseHPlus), ROXplusL, 25 μL 2 × TaqMasterMix, and 22 μL water, making a total of 50 μL.…”
Section: Methodsmentioning
confidence: 99%
“…Javed et al (2021) confirmed that the abundance of Actinobacteria bacteria can promote the formation of humus and decomposition of organic matter in soil, and also have a certain effect on the soil N cycle. As Actinobacteria tends to grow in soil with low SOM content, film mulching reduces the organic carbon content of rhizosphere soil, which is conducive to promoting the growth and propagation of Actinobacteria (Chen et al, 2017). According to Blast analysis, Nitrososphaerota is an important strain of AOA, and Nitrososphaera belongs to Nitrososphaerota.…”
Section: Effects Of Irrigation Methods On the Composition Of Ammonia-...mentioning
confidence: 99%